Sulphide textures and compositions associated with the hydrothermal/magmatic system of the Twangiza gold deposit (South Kivu, DRC) - Busane, Emmanuel Aganze (Rhodes University, Faculty of Science, Department of Geology, 2019)
Twangiza mine is a gold deposit situated in the eastern Democratic Republic of Congo. The rock types at the Twangiza Mine consist of black shale, including carbonaceous mudstone and thin intercalated layers of siltstone, and feldspar-rich granitoid intrusive sills, referred to as albitite, folded into a major antiformal structure. The gold mineralization at the mine is commonly found associated with sulphides. The sulphide textures and compositions of mineralized and unmineralized samples of black shales, albitite sills and hydrothermal veins in the mine are considered for the understanding of the spatial association of gold with sulphides and gold mineralization history of the mine. The sulphides within the Twangiza mine consist of pyrite, arsenopyrite, pyrrhotite, chalcopyrite and rare cobaltite. The primary pyrite texture occurs in unmineralized black shale and is interpreted to be diagenetic. It consists of fine-grained anhedral pyrite crystals aggregating into spherical nodules and formed in replacement of organic material during the diagenesis process. The secondary pyrite textures resulted from the hydrothermal fluids activity and include (i) aggregates of annealed anhedral crystals into sulphide-rich lenses; (ii) elongated anhedral pyrite in the form of short stringers; (iii) fine-grained subhedral to euhedral pyrite randomly distributed within the rock matrix; (iv) euhedral zoned pyrite crystals occurring within veins; (v) aggregations of fine-grained anhedral pyrite, locally distributed in the matrix; (vi) abundant dissemination of fine-grained subhedral to anhedral pyrite crystals within the vein selvedge in the host rock; (vii) and coarse-grained massive pyrite bodies. The pyrite major elemental composition does not vary significantly in the different textures and sample types. The Fe content ranges from 44.57 to 46.40 wt. %, and the S content ranges from 53.75 to 55.25 wt. %. Pyrite from mineralized black shale and hydrothermal veins contains relatively higher concentrations of As (~ 1 wt. %) than pyrite from other sample types. The arsenopyrite commonly occurs as fine-grained anhedral crystals as inclusions within pyrite, medium-grained crystal intergrowing with pyrite and/or as coarse-grained massive arsenopyrite bodies in the massive sulphide veins. The arsenopyrite composition is uniform in all textural and sample type with Fe content ranging from 33.44 to 35.20 wt. %, S content ranging from 21.13 to 22.55 wt. % and As content ranging from 42.20 to 43.97 wt. %. In mineralized black shale and unmineralized black shale, the arsenopyrite shows, however, minor concentrations of Ni with 0.39 and 0.70 wt. % respectively. The pyrrhotite occurs as fine-grained anhedral patchy crystals randomly distributed within the rock matrix of unmineralized black shale and unmineralized granitoid, and / or as inclusions within pyrite in mineralized granitoid. The pyrrhotite shows a uniform composition in all samples and textural types, though minor concentrations of Ni (2.06 wt. %) content are reported in unmineralized granitoid. Chalcopyrite occurs as fine-grained crystals in inclusions within pyrite; and cobaltite occurs as rare fine-grained anhedral crystals occasionally disseminated in the albitite sill matrix. The chalcopyrite composition does not vary considerably in all sample and textural types, and cobaltite shows minor concentrations of Ni (4.55 wt. %) and Fe (3.45 wt. %). Native gold grains are commonly found associated with the secondary pyrite texture especially within the sulphide-rich lenses and in the massive sulphide veins, and are almost pure with ~97 wt. %. A Na-rich hydrothermal fluid from low-grade metamorphism associated with the E-W compressive tectonic event, which caused formation of the antiform structure which control the mineralization in the deposit area, led to the albitization of the deposit rocks and specially the alteration of the granitic assemblage to form albitite, and the deposition of aggregates of fine-grained anhedral crystals and growth and annealing of pyrite in sulphide-rich lenses. Afterward, the CO2-rich hydrothermal fluids influx circulated through reactivated structures, including quartz veins, and led to the precipitation of dolomite, ankerite, siderite and magnesite. They also led to the precipitation of pyrite of secondary textures as well as arsenopyrite, chalcopyrite and formation of pyrrhotite from the desulphurization of early pyrite. The CO2-rich hydrothermal fluids probably leached gold and other trace elements such as As, Co, etc. from the sedimentary host rocks and deposited them into suitable traps, such as the sulphide-rich lenses and massive sulphide bodies, preferably within the hinge zone of anticline axis constituting a hydrothermal fluid pathway.
Keywords: Gold mines and mining -- Congo (Democratic Republic); Geology -- Congo (Democratic Republic); Hydrothermal alteration -- Congo (Democratic Republic); Sulphide minerals -- Congo (Democratic Republic); Gold ores -- Geology -- Congo (Democratic Republic); Geochemistry -- Congo (Democratic Republic); Twangiza Mine (Congo (Democratic Republic))